Faktor-Faktor Yang Berhubungan Dengan Perilaku Pencegahan Ulkus Diabetikum Pada Penderita Diabetes Mellitus - Oktorina, Rola; Wahyuni, Aria; Harahap, Ervina Yanti (REAL in Nursing Journal, 2019)
DM sufferers continue to increase every year. Diabetic ulcers are a common complication that often occurs in DM patients. complications prevention behavior that must be performed by DM patients in order to prevent complications. This study aims to determine the factors related to the behavior of prevention of diabetic ulcers in patients with diabetes mellitus at Achmad Mochtar Bukittinggi Hospital in 2019This type of research is analytic descriptive with cross sectional study approach. The population in this study was 334 people. Sampling using accidental sampling technique with a sample size of 35 people. Data collection in this study used a questionnaire sheet. Data analysis included univariate and bivariate analyzes using the chi-square test.The results showed that 62.9% of respondents had low knowledge, 88.6% had no ulcers, 51.4% were low socioeconomic. The results of bivariate analysis showed that there was a relationship between knowledge (p = 0.038, OR = 6) and socioeconomic status (p = 0.028, OR = 6.417) with the prevention behavior of diabetic ulcer complications, whereas the ulcer experience variable was not related to the prevention behavior of diabetic ulcer complications (p = 0.619).It was concluded that knowledge and socioeconomic status were significantly related to the prevention of diabetic ulcers in DM patients. It is expected that all parties, especially health workers, will maximize education and counseling for DM patients, especially in the low knowledge group and with low socioeconomic status.